Integration of sales and marketing : case studies of two Swedish companies - Vretborn, Joel; Åström, Linus (2008)
In a world where markets are characterized by ever increasing competition, companies have to focus all of their marketing and sales activities in the same direction in order to survive. Recent research has shown that for a company to be successful, the marketing and sales functions need to be coordinated. A company with separated marketing and sales departments will have problems competing in today’s market. Marketing and sales functions need to be integrated to some extent in all companies. There are a number of factors identified by researchers as affecting the integration of the two functions. There are also ways to improve the integration by enhancing communication or by physically integrating them. The purpose of this study is to gain a deeper understanding of the integration of the marketing and sales functions in a company. Two major companies in the refined steel industry situated in Luleå, Sweden, were studied. The findings confirm most of the established theories and describe how sales influence the strategic choices made by the marketing department. It also shows that the integration of the two functions may differ between companies. If the marketing department is well developed, it is more separated from the sales department but also in constant collaboration with them. If the marketing department is smaller, they are more dependent on the sales department and are therefore naturally integrated. The findings further shows that companies that have people with marketing background in their sales department have it easier communicating between departments and prevent conflicts due to misunderstandings. Validerat; 20101217 (root)